Methylprednisolone in patients undergoing cardiopulmonary bypass (SIRS): a randomised, double-blind, placebo-controlled trial. Issue 10000 (26th September 2015) - Whitlock, Richard P; Devereaux, P J; Teoh, Kevin H; Lamy, Andre; Vincent, Jessica; Pogue, Janice; Paparella, Domenico; Sessler, Daniel I; Karthikeyan, Ganesan; Villar, Juan Carlos; Zuo, Yunxia; Avezum, Álvaro; et al.
Summary: Background: Cardiopulmonary bypass initiates a systemic inflammatory response syndrome that is associated with postoperative morbidity and mortality. Steroids suppress inflammatory responses and might improve outcomes in patients at high risk of morbidity and mortality undergoing cardiopulmonary bypass. We aimed to assess the effects of steroids in patients at high risk of morbidity and mortality undergoing cardiopulmonary bypass. Methods: The Steroids In caRdiac Surgery (SIRS) study is a double-blind, randomised, controlled trial. We used a central computerised phone or interactive web system to randomly assign (1:1) patients at high risk of morbidity and mortality from 80 hospital or cardiac surgery centres in 18 countries undergoing cardiac surgery with the use of cardiopulmonary bypass to receive either methylprednisolone (250 mg at anaesthetic induction and 250 mg at initiation of cardiopulmonary bypass) or placebo. Patients were assigned with block randomisation with random block sizes of 2, 4, or 6 and stratified by centre. Patients aged 18 years or older were eligible if they had a European System for Cardiac Operative Risk Evaluation of at least 6. Patients were excluded if they were taking or expected to receive systemic steroids in the immediate postoperative period or had a history of bacterial or fungal infection in the preceding 30 days. Patients, caregivers, and those assessing outcomes were masked to allocation. The primary outcomes were 30-day mortality and a composite of death and major morbidity (ie, myocardial injury, stroke, renal failure, or respiratory failure) within 30 days, both analysed by intention to treat. Safety outcomes were also analysed by intention to treat. This study is registered with ClinicalTrials.gov, number NCT00427388 . Findings: Patients were recruited between June 21, 2007, and Dec 19, 2013. Complete 30-day data was available for all 7507 patients randomly assigned to methylprednisolone (n=3755) and to placebo (n=3752). Methylprednisolone, compared with placebo, did not reduce the risk of death at 30 days (154 [4%] vs 177 [5%] patients; relative risk [RR] 0·87, 95% CI 0·70–1·07, p=0·19) or the risk of death or major morbidity (909 [24%] vs 885 [24%]; RR 1·03, 95% CI 0·95–1·11, p=0·52). The most common safety outcomes in the methylprednisolone and placebo group were infection (465 [12%] vs 493 [13%]), surgical site infection (151 [4%] vs 151 [4%]), and delirium (295 [8%] vs 289 [8%]). Interpretation: Methylprednisolone did not have a significant effect on mortality or major morbidity after cardiac surgery with cardiopulmonary bypass. The SIRS trial does not support the routine use of methylprednisolone for patients undergoing cardiopulmonary bypass. Funding: Canadian Institutes of Health Research.